Superconducting state generated dynamically from distant pair source and drain - E S Ma; Z Song (New Journal of Physics, 2024)
It has been well established that the origin of p -wave superconductivity is the balance between pair creation and annihilation, described by the spin-less fermionic Kitaev chain model. In this work, we study the dynamics of a composite system where the pair source and drain are spatially separated by a long distance. We show that this non-Hermitian system possesses a high-order exceptional point (EP) when only a source or drain is considered. The EP dynamics provide a clear picture: A pair source can fully fill the system with pairs, while a drain can completely empty the system. When the two coexist simultaneously, the dynamics depend on the distance and the relative phase between the pair creation and annihilation terms. Analytical analysis and numerical simulation results show that the superconducting state can be dynamically established at the resonant pair source and drain: from an initial empty state to a stationary state with the maximal pair order parameter. It provides an alternative way of understanding the mechanism of the nonequilibrium superconducting state.